The Influence of Price, Service Quality and Brand Image on Consumer Satisfaction in Restaurants: Pengaruh Harga, Kualitas Pelayanan dan Citra Merek Terhadap Kepuasan Konsumen pada Rumah Makan - Faizah, Ghifari Nur; Astuti, Mudji (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the effect of price on consumer satisfaction, the effect of service quality on consumer satisfaction and the effect of brand image on consumer satisfaction at the Janur Kuning Restaurant in Gempol. Methods This research uses a quantitative approach. Data collection techniques by distributing questionnaires. The population in this study is the Consumers of the Yellow Janur Restaurant in Gempol. The number of samples taken in this study were 97 respondents. The sampling technique used non-probability sampling technique with the type of accidental sampling technique. The analysis technique used in this research is multiple linear regression. The results showed that price had an effect on consumer satisfaction, service quality had an effect on consumer satisfaction and brand image had an influence on consumer satisfaction and the simultaneous test showed that price, service quality and brand image had a simultaneous influence on consumer satisfaction at the Janur Kuning Restaurant in Gempol.